Black Sea Methane Flares From the Seafloor: Tracking Outgassing by Using Passive Acoustics - Longo, Manfredi; Lazzaro, Gianluca; Caruso, Cinzia Giuseppina; Radulescu, Vlad; Radulescu, Raluca; Sciré Scappuzzo, Sergio Simone; Birot, Dominique; Italiano, Francesco (Frontiers in Earth Science, 2021)
The Black Sea bottom is well known to be earth's largest anaerobic methane source, hosting a huge amount of cold seeps releasing significant volumes of methane of both thermogenic and biogenic origin. Taking into account the well-known effects of methane concerning global warming, including the warming up of the oceans, an effective monitoring of its output from the Black Sea is nowadays an essential target for interdisciplinary studies. We discuss the results achieved during monitoring campaigns aimed to detect and track methane flares from the seafloor of the Romanian sector of the Black Sea, in order to better constrain the possible mechanisms responsible for its injection from the marine sediments, through the water column, into the atmosphere. In the mainframe of the ENVRI-Plus project, we deployed a multidisciplinary seafloor observatory for short, mid and long time monitoring and collected samples of the water column. The multidisciplinary seafloor observatory was equipped with probes for passive acoustic signals, dissolved CH4 and chemical-physical parameters. The collected data showed high concentration of dissolved methane up to values of 5.8 micromol/l. Passive acoustics data in the frequencies range 40-2500 Hz allow us to discriminate different degassing mechanisms and degassing styles. The acoustic energy associated with gas bubbling is interpreted as a consequence of the gas dynamics along the water column while the acoustic range 2-20 Hz reveals vibration mechanisms generated by gas dynamic’s along the cracks and inside the sediments.